Khul‘ in Action: How Do Local Muslim Communities in Germany Dissolve an Islamic Religious-Only Marriage? - Jaraba, Mahmoud (Journal of Muslim Minority Affairs, 2020)
Relying upon extensive ethnographic field-collected data as well as 51 privately performed documents of khul‘ (divorce initiated by a woman), this article addresses two questions. Firstly, how have practices of khul‘ among local Muslim communities been influenced by Germany's secular state framework? Secondly, how do local religious actors develop extrajudicial religious forms of mediation and arbitration, often taking place in a mosque or a private place, in order to fulfil certain aspects of sharīʿah? The paper argues that the absence of a recognised Islamic judicial authority or formally recognised Islamic mediation and arbitration service in Germany has led Muslim communities to come up with “local experts”, who purport to implement elements of sharīʿah through informal mediation and arbitration. This leads to new religious actions and norms which might, in the future, lead to normalised new practices in countries such as Germany where Muslims are a minority.
Created from Fastlane, Scopus look-up
Keywords: arbitration; European Muslims; imams; Islam in Germany; khul‘; mediation; new anthropology of Islam; sharīʿah; ḥaḍāna; ṭalāq